Ensuring Sustained Beneficial outcomes for water and sanitation (WATSAN) programmes in the developing world. - Mathew, Brian (Cranfield University, 2004)
The two objectives of this thesis are firstly to suggest approaches to achieve sustained beneficial outcomes from WATSAN, and secondly how to ‘scale up’ application of these approaches, so that they impact positively on the lives of the millions of people who live without safe water or adequate sanitation. To discover what these approaches are the literature is examined and practical lessons are drawn from two WATSAN programmes in East and Central Africa. The conclusions are presented in the form of a charter for the sustainable development of WATSAN, with nine clauses suggested to guide project and programme managers around the issues that need to be taken into account in this most important of development sectors. The charter’s clauses walk the reader through various stages of WATSAN development, through participatory project identification, need and demand response, sustainable environmental approaches, structured health education, staffing issues, decentralisation, and the practicalities of policy, allowing work to progress at the speed that communities need to acquire ownership whilst at the same time scaling up programme implementation to make a meaningful impact on the MDGs. The global issues of financing the MDGs are also assessed, and the conclusion is that meeting the MDGs is possible in sustainable manner, but only if there is a massive shift in the resources allocated towards those really in need, and a change in the attitudes of the political power brokers to allow this, promoting quality work, to be implemented by integrated teams, in a process orientated, ethos driven way, with WATSAN set as a keystone of wider human development.